The Governance Regime of the Mekong River Basin Can the Global Water Conventions Strengthen the 1995 Mekong Agreement? - Kinna, Rémy (Brill Research Perspectives in International Law, 2017)
The Governance Regime of the Mekong River Basin provides a comparative analysis of the global water conventions and the 1995 Mekong Agreement, whereby, the authors strongly recommend Mekong states joining both conventions in order to buttress and clarify the Agreement.; Readership: Scholars and practitioners in the field of international water law and anyone concerned with the legal framework and governance regime of the Mekong River and its tributaries.